2020
DOI: 10.1186/s12934-020-01488-w
|View full text |Cite
|
Sign up to set email alerts
|

Designing next generation recombinant protein expression platforms by modulating the cellular stress response in Escherichia coli

Abstract: Background A cellular stress response (CSR) is triggered upon recombinant protein synthesis which acts as a global feedback regulator of protein expression. To remove this key regulatory bottleneck, we had previously proposed that genes that are up-regulated post induction could be part of the signaling pathways which activate the CSR. Knocking out some of these genes which were non-essential and belonged to the bottom of the E. coli regulatory network had provided higher expression of GFP and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the double knockout mutant BW25113ΔelaA + ΔcysW (DKO) had the highest activity in asparaginase production with 70.3 units/ml. To further unravel the mechanisms involved in CSR mitigation by the DKO strain, Guleria et al [65] used the strain to overexpress the Rubella E1 gene and performed a transcriptome analysis. Compared to the wild type, down-regulation of multiple genes related to growth-critical processes was suppressed in the DKO strain, including translation, transcription, RNA and ribosome biogenesis, transport, energy metabolism and other catabolic processes.…”
Section: Balancing Cell Growth and Recombinant Protein Productionmentioning
confidence: 99%
“…The results showed that the double knockout mutant BW25113ΔelaA + ΔcysW (DKO) had the highest activity in asparaginase production with 70.3 units/ml. To further unravel the mechanisms involved in CSR mitigation by the DKO strain, Guleria et al [65] used the strain to overexpress the Rubella E1 gene and performed a transcriptome analysis. Compared to the wild type, down-regulation of multiple genes related to growth-critical processes was suppressed in the DKO strain, including translation, transcription, RNA and ribosome biogenesis, transport, energy metabolism and other catabolic processes.…”
Section: Balancing Cell Growth and Recombinant Protein Productionmentioning
confidence: 99%
“…In Escherichia coli , it has been shown that co-expression of critical factors such as chaperones can unburden the metabolic load which helps to increase the product yield when folding and solubility is crucial ( 6–9 ). In contrast, down-regulation or even knockouts of proteases provides better stability of the product ( 4 , 10–12 ). However, the specific factors that improve the production process performance are manifold and largely unknown.…”
Section: Introductionmentioning
confidence: 99%